Water Consumption and Long-Run Urban Development: The Case of Milan - Mario Nosvelli; Antonio Musolesi (Fondazione Eni Enrico Mattei (FEEM), 2005)
Analyses of long run consumption series are rare in literature. We study the evolution of water consumption in Milan in the twentieth century. The objective is twofold: on one side, the univariate analysis tries both to assess the impact of relevant socio-economic and environmental changes on water consumption in Milan and verify if consumers have deeply rooted consumption habits. On the other side, the multivariate analysis is used to identify the socio-economic factors that are relevant in explaining consumption evolution. Results indicate both that water users have well entrenched consumption habits and that population, climate and economic structure behave more similarly, in Euclidean terms, to water consumption than to other economic and social variables.
Keywords: Q25; R1; C22; C19; 330; Urban consumption; Long-run; Development; Environmental changes; Wasserversorgung; Stadtentwicklung; Umweltbelastung; Mailand